More experiments may help explore what works in conservation - Jones, Julia (New Zealand Science Review, 2018)
All over the world, countless conservation projects are taking place, attempting to achieve aims from reducing habitat loss, to restoring populations of threatened species. However there is growing awareness that conservationists have not always done a good enough job at evaluating whether the things they do really work. Efforts that fail to make things better for species and ecosystems waste the limited resources available for conservation, and result in missed opportunities to stem the loss of biodiversity. Given that monitored populations of wildlife species have declined by 60% in the last 50 years, and large-scale loss of forest continues, this is bad news. So, research to show whether conservation efforts work really matters. And those doing conservation need easy access to the results of this vital evidence. In many fields, when researchers want to know whether something works they conduct an experiment. For example, patients are often randomly assigned to receive a new drug (or not) and the results are compared to determine if the new treatment has the potential to help people. Despite calls for more use of experiments in conservation, they remain extremely rare. The following article is republished from The Conversation, dated 6 November 2018. The article has not been edited, but we have attributed the author and her institute, given the internet citations, and used a non-copyrighted illustration.